2016
DOI: 10.1364/ol.41.001321
|View full text |Cite
|
Sign up to set email alerts
|

Bit-efficient, sub-millisecond wavefront measurement using a lock-in camera for time-reversal based optical focusing inside scattering media

Abstract: Time-reversed ultrasonically encoded optical focusing measures the wavefront of ultrasonically tagged light, and then phase conjugates the tagged light back to the ultrasonic focus, thus focusing light deep inside the scattering media. In previous works, the speed of wavefront measurement was limited by the low frame rates of conventional cameras. In addition, these cameras used most of their bits to represent an informationless background when the signal-to-background ratio was low, resulting in extremely low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 24 publications
0
37
0
Order By: Relevance
“…Specifically, a digital camera is used to measure the wavefront of the scattered light with digital holography. Then, an SLM, with pixels that are one-to-one matched with the pixels of the camera by a camera lens, is used to reconstruct the conjugate wavefront of the scattered light to achieve optical phase conjugation/time reversal [11,12,23,24,3234]. In most wavefront shaping experiments, nematic liquid crystal based SLMs (NLC-SLMs) are used for phase modulation [79,11,12].…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, a digital camera is used to measure the wavefront of the scattered light with digital holography. Then, an SLM, with pixels that are one-to-one matched with the pixels of the camera by a camera lens, is used to reconstruct the conjugate wavefront of the scattered light to achieve optical phase conjugation/time reversal [11,12,23,24,3234]. In most wavefront shaping experiments, nematic liquid crystal based SLMs (NLC-SLMs) are used for phase modulation [79,11,12].…”
Section: Methodsmentioning
confidence: 99%
“…To take full advantage of the SLM and further improve the speed of ultrasound-guided DOPC, we develop a double-exposure binary wavefront measurement method. The speed of our system is one to two orders of magnit ude higher than those of previous ultrasound-guided DOPC systems [16,2431], and our method achieves the fastest light focusing inside a scattering medium among all the digital wavefront shaping methods developed to date [36]. …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…To achieve wavefront shaping, it is required to determine the optimum wavefront and shape the incident light before the speckle pattern associated with the scattering medium decorrelates [13][14][15] . However, even for ex vivo biological tissue, it has been shown that the speckle correlation time decreases as the scattering medium becomes thick 16,17 , due to the Brownian motion of the scatterers.…”
Section: Speckle Correlation Timementioning
confidence: 99%
“…In this work, we overcome the above drawbacks in heterodyne holography based UOT by using a lock-in camera [31][32][33] (heliCam C3, Heliotis; 300 Â 300 pixels, 40 lm pixel size), in which each pixel performs analog lock-in detection and outputs only the information of the AC signal, with a frame rate of up to 3800 frames per second to an on-chip memory. Specifically, the lock-in circuitry generates the in-phase (S I ðr i Þ) and the quadrature (S Q ðr i Þ) components of the AC signal for each pixel with a position of r i , i ¼ 1, 2,…, 300 Â 300, which are digitized by a 10-bit ADC.…”
mentioning
confidence: 99%